Basal haemoglobin levels as prognostic factor for early death in elderly patients with a hip fracture – A twenty year observation study. Issue 6 (June 2015) - Kovar, Florian M.; Endler, Georg; Wagner, Oswald F.; Jaindl, Manuela
Abstract: Introduction: Hip fractures are a significant cause of mortality and morbidity in the elderly. This study investigated the relationship between initial haemoglobin (Hb) levels and a prognostic parameter for outcome in those patients. Patients and methods: A total of 3595 consecutive patients with diagnosed hip fractures were included in our study (72.2% females). Anaemia was defined according to WHO criteria, with according subgroups mild, moderate and severe anaemia. Data collection was performed prospectively and statistical evaluation was performed retrospectively. Results: Mean follow up in our study group was 11.2 ± 0.3 months. The mean age of our study group was 78.5 years (SEM ± 0.2 years). To facilitate analysis, patients were divided in two groups: ≤84 years (60.1%) and ≥85 years (39.9%). Mortality <12 months was 12.2% ( n = 439). In our study population lower Hb levels ad admission were associated with a markedly elevated short-term mortality. In a multivariate logistic regression model adjusted for age and sex, mild anaemia at admission caused a 1.5 (CI: 1.1–1.9), moderate anaemia a 2.6 (95 CI: 2.0–3.4), and severe anaemia a 3.6 (CI: 1.8–6.9) fold increase in three months mortality compared to patients without anaemia. Total lymphocyte count (1.2 ± 0) did not show any differences between the subgroups. Conclusion: Those findings in our study population with 3595 patients over a period of twenty years have proven that initial Hb levels are a useful and cost effective parameter to predict mortality in elderly patients with a hip fracture. This prognostic factor may help to increase the outcome of elderly patients with a hip fracture.